Pengaruh Kualitas Pelayanan Terhadap Kepuasan Pasien Di RSUD Sragen - Winarno, Tri; , Basworo Dibyo, S.E, M.Si (2015)
This study attempts to find out if dimension in the quality of service that is tangibles , reliability , responsiveness , assurance and emphaty impact on customer satisfaction and analyze factors most dominant in effecting patient satisfaction rsud sragen .The population in this research are cases of patients who use services rsud sragen .Sample in extract as many as 100 respondents using non-probability techniques of sampling accidental with the approach of sampling , namely the determination of sampling techniques based on chance meeting with scientists could only sampled if it were viewed suitable .Based on the results of the analysis it is found that the tangibles variables , reliability , responsiveness , assurance and emphaty impact on customer satisfaction regression analysis liniear worship of idols obtained the equation as follows: Y = 10,188 + 0,165x1 + 0,158x2 + 0,346x3 + 0,630x4 + 0,394x5 .T produce with the tangibles of 1,914 thitung for variables 1,885; ; reliability of assurance of responsiveness by 1,707; emphaty of 2,975 4,762 and .Thus it appears that the value of the regression coefficient is variable variable highest value the coefficient of assurance Key words : Tangibles, Reliability, Responsiveness, Assurance, Emphaty Customer Satifaction